Application of geopolymer concrete (Международный научный журнал «Инженер», 2026)
The requirement for concrete is growing daily and cement is utilized for meeting the needs of infrastructure facility development. One ton of cement production generates one ton of CO2, which negatively impacts the environment. To decrease the utilization of Ordinary Portland Cement and CO2 generation, innovative next-generation concrete has been created, such as Geopolymer concrete. It employs fly ash and alkaline solution as its Binding Materials. Geopolymer necessitates oven curing in temperature ranges from 60° C to 100° C for a duration of 24 to 96 hours. This paper determined that all investigators have devoted their efforts to demonstrate the influence of Ground Granulated Blast Slag on Geopolymer Concrete. Nevertheless, it should be noted that modifications in parameters like Na2SiO3/NaOH Proportion, Molarity of NaOH, Curing temperature, and Curing time create Variations in the Strength. Substitution of Fly ash with Ground Granulated Blast Slag progressively enhances the Strength without Oven curing provision. An insufficiency of information regarding certain aspects of geopolymerisation has become evident, and the scientific community should concentrate on these gaps.